Comparison of Wheel Odometry and Visual Odometry for Low-Cost Vehicle Navigation - Rezende, Gabriel Lima; Silva, Felipe O.; Marques, Leomar S. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS); 2024: Anais do XVI Simpósio Brasileiro de Robótica e XV Workshop de Robótica na Educação, 2024)
This paper presents a comparative study of Wheel Odometry (WO), which relies on measurements from wheel en-coders, and Visual Odometry (VO), which uses images captured by a monocular camera to estimate the vehicle movement, for the purpose of low-cost vehicle navigation. The analysis reveal the strengths and limitations of each method, offering insights into their suitability for different applications. The ultimate goal of the paper is to guide the selection of odometry techniques in designing low-cost, efficient vehicle navigation systems. Results from simulated experiments suggest that, while VO can offer higher accuracy in complex environments, WO remains a viable and cost-effective option for simpler navigation tasks, especially when the associated wheel radius errors are correlated, i.e., similar for both wheels, and do not exceed ±0.26%.